Tinjauan Yuridis Kafaah dalam Perkawinan Antar Negara: Internalisasi dalam Ius Constituendum - Rayhan Gunawan Sejahtera; Tubagus Farhan Maulana (Syakhsiyah Jurnal Hukum Keluarga Islam, 2025)
This study aims to analyze the concept of kafaah in Islamic law and its relevance to the fundamental values of the Indonesian state within the context of positive law. The research highlights the challenges in implementing the principle of kafaah in transnational marriages, with comparative insights from several Islamic countries. A qualitative approach based on juridical-normative methods was employed to explore how kafaah can be internalized within the national legal system without disregarding the diversity of customs and cultural traditions in Indonesian society. The findings indicate that although kafaah is not explicitly regulated in Law No. 1 of 1974 on Marriage, the principle remains relevant as a guideline for fostering harmony within the family. In Indonesia, the application of kafaah can be aligned with the values of Pancasila, which uphold justice, equality, and tolerance. The study concludes that the internalization of kafaah into Indonesia's positive law requires a comprehensive approach encompassing philosophical, sociological, and juridical dimensions. This approach is expected to address contemporary needs and establish a legal system that supports family harmony in accordance with Islamic and Indonesian values.